Ion energy distributions and densities in the plume of Enceladus. (1st October 2016) - Sakai, Shotaro; Cravens, Thomas E.; Omidi, Nojan; Perry, Mark E.; Waite, J. Hunter
Abstract: Enceladus has a dynamic plume that is emitting gas, including water vapor, and dust. The gas is ionized by solar EUV radiation, charge exchange, and electron impact and extends throughout the inner magnetosphere of Saturn. The charge exchange collisions alter the plasma composition. Ice grains (dust) escape from the vicinity of Enceladus and form the E ring, including a portion that is negatively charged by the local plasma. The inner magnetosphere within 10 RS (Saturn radii) contains a complex mixture of plasma, neutral gas, and dust that links back to Enceladus. In this paper we investigate the energy distributions, ion species and densities of water group ions in the plume of Enceladus using test particle and Monte Carlo methods that include collisional processes such as charge exchange and ion-neutral chemical reactions. Ion observations from the Cassini Ion and Neutral Mass Spectrometer (INMS) for E07 are presented for the first time. We use the modeling results to interpret observations made by the Cassini Plasma Spectrometer (CAPS) and the INMS. The low energy ions, as observed by CAPS, appear to be affected by a vertical electric field ( E Z =−10 µV/m) in the plume. The E Z field may be associated with the charged dust and/or the pressure gradient of plasma. The model results, along with the results of earlier models, show that H3 O + ions created by chemistry are predominant in the plume, which agrees with INMS and CAPS data, but the INMS count rate in the plume for the model is several times greater than the data, which we do not fully understand. This composition and the total ion count found in the plume agree with INMS and CAPS data. On the other hand, the Cassini Langmuir Probe measured a maximum plume ion density more than 30, 000 cm −3, which is far larger than the maximum ion density from our model, 900 cm −3 . The model results also demonstrate that most of the ions in the plume are from the external magnetospheric flow and are not generated by local ionization. The origin of the ions in the plume was investigated using two different velocity models. Most ions were created by the interaction with background magnetospheric plasma and by photoionization. INMS and CAPS also detected water cluster ions. We will interpret these observations as a result of ion collisions with neutral water clusters, (H2 O)n, originating in the tiger stripe vents as suggested by Tokar et al. (2009). We also estimated the process of generating cluster ions based on the INMS observations. We suggest that the most likely source is reaction of H3 O + with neutral water clusters or dimers such as (H2 O)2 formed in the plume vents. Highlights: Ions in the Enceladus plume were studied using a test particle model and INMS data. Vertical electric fields generate low ion energies in agreement with CAPS detections. H3 O + ions created by chemistry are predominant in the plume. The maximum ion density from our model was 400–900 cm −3 . Cluster ions are created by reaction of H3 O + with neutral water clusters or dimers.